Licensing occupations : ensuring quality or restricting competition? - Kleiner, Morris M. (W.E Upjohn Inst. for Employment Research KalamazooUS, 2006)
Presents new analysis and evidence on the productivity effects of licensing while detailing its price and labour market impacts.